The Effect of Segregation on Intergroup Relations - Enos, Ryan D.; Celaya, Christopher (Journal of experimental political science, 2018)
Inter-ethnic residential segregation is correlated with intergroup bias and conflict, poorly functioning states and civil societies, weak economic development, and ethnocentric political behavior. As such, segregation has been a subject of long-standing interest. However, segregation has not been assigned in randomized controlled trials, so the observed correlations may be spurious and the mechanism behind these correlations is poorly understood. In two experiments, we randomly assign segregation in a laboratory and demonstrate that segregation affects perceptions of other people and causes intergroup bias in costly decision-making. Rather than segregation merely inhibiting intergroup contact, we demonstrate that segregation directly affects perception and thus can affect intergroup relations even when holding contact constant.